Key factors affecting hydrocarbon accumulation in ancient dolomite gas reservoirs of Xixiangchi formation (Southern Sichuan Basin, China) - Hu, Xiuquan; Luo, Wei; Zang, Dianguang; Wang, Wenzhi; Yi, Chi; Li, Jianghan (Frontiers in Earth Science, 2023)
The Upper Cambrian Xixiangchi Formation in the southern Sichuan Basin, China, has favorable hydrocarbon accumulation conditions. The accumulation factors and enrichment conditions of this formation were key considerations in this study. By analyzing core, thin section, seismic, and geochemical data, we demonstrate that the granular and crystalline dolomite in the Xixiangchi Formation are characterized by vertical, overlapping development and low single-reservoir thickness. During the transformation of karst and tectonism, dissolution pores and fractures developed to form an ideal reservoir space. The reservoir of the Xixiangchi Formation is connected to the Lower Cambrian source rock through a fault system. The high-energy shoal facies of the Xixiangchi Formation are located on the oil and gas migration path, providing an appropriate reservoir space for forming the source reservoir configuration relationship between the lower generation and upper reservoir. The key factors affecting hydrocarbon accumulation in the Xixiangchi Formation are sufficient oil and gas supply, development of inherited paleo-uplift, effective transportation system, and favorable reservoir-forming combination. The inherited paleo-uplift controls the distribution of gas reservoirs. Owing to the short migration distance of oil and gas, hydrocarbon is found near source hydrocarbon accumulation, and the paleo-uplift slope area should be targeted for exploration in future studies.